2003
DOI: 10.1007/s00066-003-1106-0
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Simultaneous Radiochemotherapy with Cisplatin and Paclitaxel in Combination with Accelerated Hyperfractionated Radiotherapy in Locally Advanced Head and Neck Tumors

Abstract: This very aggressive sRCT protocol yielded excellent response and survival figures but was associated with a very high rate of acute toxicity (8% therapy-related deaths). A maximal supportive treatment is therefore required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 29 publications
0
22
0
2
Order By: Relevance
“…In 2003, Kuhnt et al [11] proposed a concurrent chemoradiation in which cisplatin (20 mg/m²/day) was administered on days 1-5 and 29-33 and paclitaxel (25 mg/m²/ day) was administered twice weekly for 12 cycles. This treatment led to the development of severe acute skin (grade 3: 22%) and mucosal toxicity (grade 3: 57%).…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, Kuhnt et al [11] proposed a concurrent chemoradiation in which cisplatin (20 mg/m²/day) was administered on days 1-5 and 29-33 and paclitaxel (25 mg/m²/ day) was administered twice weekly for 12 cycles. This treatment led to the development of severe acute skin (grade 3: 22%) and mucosal toxicity (grade 3: 57%).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, randomized studies have demonstrated the superiority of radiotherapy in combination with chemotherapy over radiotherapy alone. RCT with multiagent chemotherapy, or with hyperfractionated radiotherapy, may lead to even better outcomes, although toxicity may be increased [2,3,8,11,14,15,17,18,20,22,25,32].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, concomitant chemoradiation is currently considered a standard treatment for patients with locally advanced nasopharyngeal cancer [5,8,19,29].…”
Section: Discussionmentioning
confidence: 99%